2000
DOI: 10.1177/026765910001500207
|View full text |Cite
|
Sign up to set email alerts
|

Size makes a difference: use of a low-prime cardiopulmonary bypass circuit and autologous priming in small adults

Abstract: Low hematocrit (Hct < 20) during cardiopulmonary bypass (CPB) is associated with higher mortality and other adverse outcomes. More frequently, low Hct is encountered in patients with small body size and women patients. This prompted us to take an aggressive approach in our care of these patients, involving a strategy for predicting patients at risk of low Hct, with the aid of an electronic worksheet that accurately predicts CPB Hct, and two prevention strategies: use of a low-prime CPB circuit (LP) for all adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 13 publications
(13 reference statements)
1
42
2
Order By: Relevance
“…3 In order to reduce this volume, the technique of retrograde autologous priming (RAP) was successfully investigated in several studies. 1,2,4,5 RAP reduces haemodilution during the start-up phase of CPB by prior reduction of the priming volume. This is achieved by retrograde arterial or venous filling of the heart-lung machine (HLM) after cannulation, by a slow exchange of the crystalloid priming solution with the patient's own blood.…”
Section: Introductionmentioning
confidence: 99%
“…3 In order to reduce this volume, the technique of retrograde autologous priming (RAP) was successfully investigated in several studies. 1,2,4,5 RAP reduces haemodilution during the start-up phase of CPB by prior reduction of the priming volume. This is achieved by retrograde arterial or venous filling of the heart-lung machine (HLM) after cannulation, by a slow exchange of the crystalloid priming solution with the patient's own blood.…”
Section: Introductionmentioning
confidence: 99%
“…This has advantages for blood flow and organ preservation, but results in a mixture with the patient's blood, causing a hemodilution, and, paradoxically, may lead to the need for blood transfusions during surgery. Although this method is widely used as standard CPB, hemodilution is associated with significant mortality and other adverse conditions, especially when the hematocrit reaches values below 20% [1].…”
Section: Introductionmentioning
confidence: 99%
“…Retrograde autologous priming (RAP) is a method of CPB, at low cost, which has been described [1,7] as modification of the method proposed, in 1959, by Panico and Neptune [8]. Previous studies have shown that this method reduces hemodilution during CPB, the reduction of blood transfusions by increasing the hematocrit intraoperatively, especially in patients who have risk factors as anemia, small body surface area, and refuses to receive blood products [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the deleterious effects of CPB, various improvements have been made. [5][6][7][8] Utilizing these improvements, we devised a less invasive CPB (low prime volume closed CPB; LPVP). In this article, we demonstrate the decreased invasiveness and improved effi cacy of LPVP using molecular biological techniques.…”
Section: Introductionmentioning
confidence: 99%